The Influence of Public Relations Strategies and Organizational Culture on the Institutional Performance of the Garut Regional Narcotics Agency (BNNK) in Achieving Its Annual Accreditation - Fitriani Afifah; Ummu Salamah; Heri Hendrawan (Journal of Digital Marketing and Communication, 2026)
Despite the relatively good institutional performance achieved by the Garut Regional Narcotics Agency (BNNK), several challenges remained, particularly in optimizing public communication, addressing limited human resources, and strengthening organizational culture, all of which could affect institutional performance. Therefore, this study aimed to analyze the influence of Public Relations strategies and organizational culture on institutional performance at BNNK Garut. A quantitative causal research design was employed, involving all 85 employees using a census sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics version 25. The validity test confirmed that all questionnaire items were valid, while the reliability test demonstrated excellent internal consistency, with Cronbach's Alpha values of 0.970 for Public Relations strategy, 0.955 for organizational culture, and 0.932 for institutional performance. The classical assumption tests indicated that the regression model satisfied the assumptions of normality (Kolmogorov–Smirnov significance = 0.200), absence of multicollinearity (Tolerance = 0.689; VIF = 1.450), and homoscedasticity. The findings revealed that Public Relations strategy had a positive and significant effect on institutional performance, organizational culture also had a positive and significant effect, and both variables simultaneously exerted a significant influence on institutional performance. The coefficient of determination (Adjusted R² = 0.410) indicated that 41% of the variance in institutional performance was explained by Public Relations strategy and organizational culture, while the remaining 59% was attributable to other factors outside the proposed model. These findings highlighted the importance of strengthening both external communication strategies and internal organizational culture to enhance institutional performance.